Cultural Survival and the Postcolonial Imagination: A Fanonian Reading of Chinua Achebe's Things Fall Apart - Pramudya, Muh.; Puspita, Ida (Universitas Muhammadiyah Mataram, 2025)
Postcolonial literary studies have long explored how colonized subjects reclaim cultural identity and agency in response to imperial domination. However, although many formerly colonized nations have achieved political independence, the legacy of colonial knowledge and cultural domination continues to shape identities, institutions, and worldviews. Most previous studies on Things Fall Apart tend to focus on the impact of colonialism or political resistance but have not systematically examined how Fanon’s framework can be applied to analyze the process of cultural decolonization through the recovery of Igbo social structures, language, spatial values, and collective identity as forms of epistemic resistance. Drawing on Frantz Fanon’s theory of cultural decolonization, the analysis highlights how Achebe’s narrative resists colonial discourse by restoring indigenous epistemologies and reasserting communal identity. This study addresses the ongoing condition in Igbo society by offering a Fanonian reading of Chinua Achebe’s Things Fall Apart, focusing on the enduring impact of colonialism on the social structures, traditional values, and identity formations within this society.